An Evidence-Based Case Study on the Successful Non-Surgical Treatment of Bilateral Varicocele - Nargave, Shubham; Mishra, Nripendra; Patidar, Rachana; Pandey, Anurag (Journal of Neonatal Surgery, 2025)
Varicocele is characterized by abnormal dilatation and tortuosity of the veins within the pampiniform plexus of the spermatic cord. It is a relatively common clinical condition associated with scrotal pain, swelling, testicular atrophy, and infertility. Although classical Ayurvedic texts do not describe "varicocele" directly, its presentation can be closely correlated with Siraja Granthi of Vrushana Kosha (scrotal venous swelling). According to Ayurvedic principles, the vitiated Vata Dosha compresses (Sampeedya), contracts (Samkochya), and dries (Vishoshya) the venous channels, resulting in the formation of Granthi (vascular swelling or cyst-like structure). In modern medicine, surgical intervention is often considered the primary mode of treatment. However, Ayurveda offers promising non-surgical alternatives. This case study presents the management of a 30-year-old male patient who attended the Panchakarma OPD of Govt. Dhanwantari Ayurvedic Hospital, Ujjain, with complaints of scrotal pain and swelling persisting for five months. The patient was treated with Jalaukavacharana (leech therapy), Shamana Chikitsa (palliative therapy), and Patra Bandhana (herbal bandaging). A total of six sittings of Jalaukavacharana were administered. Significant reduction in symptoms, particularly pain and swelling, was observed after the second session itself. This case highlights that therupetic effect of Jalaukavacharana is a safe, cost-effective, and highly beneficial therapy for the management of varicocele. It provides an effective non-surgical option within the scope of Ayurvedic clinical practice